An empirical analysis of leadership styles and the role of organizational culture on employees’ satisfaction in Malaysian hotel industry / Norwahidah Abd Wahid - Abd Wahid, Norwahidah (Institute of Graduate Studies, UiTM, 2014)
The topics of leadership and organizational culture have fascinated considerable awareness from both academics and practitioners. The study examined the relationship of leadership style and organizational culture with employee satisfaction in the Malaysian hotel industry. As leadership style is a critical element in the success of an organization, organizational culture is also a crucial factor influencing the competitive strength of an organization. A large amount of the interest in the two areas is based on explicit and implicit claims that both leadership and culture are linked to employees’ satisfaction. Although the links between leadership and performance and between culture and job satisfaction have been looked into separately, few studies have examined the correlation between the three concepts. The research also examined the leadership style used by hotel managers and the perceptions of that leadership practices by the employees relative to their job satisfaction.